A comprehensive evaluation of measures of core inflation for Canada: An update - Helen Lao; Ceciline Steyn (Bank of Canada, 2019)
We provide an updated evaluation of the value of various measures of core inflation that could be used in the conduct of monetary policy. We find that the Bank of Canada's current preferred measures of core inflation-CPI-trim, CPI-median and CPI-common-continue to outperform alternative core measures across a range of criteria. These measures remain less biased, less volatile and much more persistent relative to alternative core measures and CPI inflation. They are also still moving with the economic cycle. Our analysis shows that historical revisions have been relatively small among these three core inflation measures since their inception and that CPI-common seems less prone to revisions and sector-specific shocks than CPI-trim and CPI-median.
Keywords: E; E3; E31; E5; E52; 330; Inflation and prices; Monetary policy framework